Cyclodimerization of stilbenes and styrenes catalyzed by heteropolyacid supported on silica - Alesso, E. N. (2000)
Several stilbenes and styrenes have been treated with heteropolyacid] (HPA) supported over silice. The compounds obtained were characterized by 1H and 13C-NMR and the yields were compared with those obtained using H2SO4 (c) and ethyl poliphosphate (PPE).